Scheme for implementing nonlocal high-fidelity quantum controlled-not gates on quantum-dot-confined electron spins using optical microcavities and photonic hyperentanglement - Han, Yu-Hong; Cao, Cong; Fan , Ling; Zhang , Ru (Frontiers in Physics, 2022)
Quantum information networks can transmit quantum states and perform quantum operations between different quantum network nodes, which are essential for various applications of quantum information technology in the future. In this paper, a potentially practical scheme for implementing nonlocal quantum controlled-not (CNOT) gate operations on quantum-dot-confined electron spins between two quantum network nodes is presented. The scheme can realize parallel teleportation of two nonlocal quantum CNOT gates simultaneously by employing hyperentangled photon pairs to establish quantum channel, which can effectively improve the channel capacity and operational speed. The core of the scheme are two kinds of photon-spin hybrid quantum CNOT gate working in a failure-heralded and fidelity-robust fashion. With the heralded mechanism, the nonlocal CNOT gates can be implementated with unity fidelities in principle, even if the particularly ideal conditions commonly used in other schemes are not satisfied strictly. Our analysis and calculations indicate that the scheme can be demonstrated efficiently (with efficiency exceeding 99%) with current or near-future technologies. Moreover, the utilized photon-spin hybrid quantum gates can be regarded as universal modules for many other quantum information processing (QIP) tasks. Therefore, the scheme is potential for constructing elementary quantum networks, and realizing nolocal QIP with high channel capacities, high fidelities, and high efficiencies.